2013
DOI: 10.1002/jmor.20184
|View full text |Cite
|
Sign up to set email alerts
|

Male internal reproductive structures of european pea crabs (Crustacea, Decapoda, Brachyura, Pinnotheridae): Vas deferens morphology and spermatozoal ultrastructure

Abstract: Pea crabs of the subfamily Pinnotherinae (Pinnotheridae) have a high investment in reproduction and an outstanding reproductive output, probably as an adaptation to the required increase in reproductive rate due to the pinnotherids small size and their parasitic, host-dependant way of life. In the present study, we investigate the male internal reproductive structures and the ultrastructure of spermatozoa of Pinnotheres pisum and Nepinnotheres pinnotheres by histological methods and both scanning- and transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Detailed information about many aspects of the association between pinnotherid crabs and their host remain to be studied (McDermott 2006, Peiró et al 2011). Several studies addressed different reproductive aspects of these symbiotic crabs, including the morphology of the reproductive system (Becker et al 2011, 2012, 2013), mating system (Dos Santos-Alves and Pezzuto 1998, Baeza 1999, Peiró et al 2013), intraspecific latitudinal effects on different reproductive attributes (Lardies and Castilla 2001), as well as fecundity (Báez and Martínez 1976, Hines 1992, Cabrera Peña et al 2001, Lardies and Castilla 2001). Our knowledge about energy allocation in embryo production of pinnotherid crabs is scarce; however, results obtained from several species of pea crabs clearly demonstrated that brood masses of these crabs are extraordinarily large in relation to female body size when compared to free-living decapods (Hines 1992, Lardies and Castilla 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information about many aspects of the association between pinnotherid crabs and their host remain to be studied (McDermott 2006, Peiró et al 2011). Several studies addressed different reproductive aspects of these symbiotic crabs, including the morphology of the reproductive system (Becker et al 2011, 2012, 2013), mating system (Dos Santos-Alves and Pezzuto 1998, Baeza 1999, Peiró et al 2013), intraspecific latitudinal effects on different reproductive attributes (Lardies and Castilla 2001), as well as fecundity (Báez and Martínez 1976, Hines 1992, Cabrera Peña et al 2001, Lardies and Castilla 2001). Our knowledge about energy allocation in embryo production of pinnotherid crabs is scarce; however, results obtained from several species of pea crabs clearly demonstrated that brood masses of these crabs are extraordinarily large in relation to female body size when compared to free-living decapods (Hines 1992, Lardies and Castilla 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results about the testes (d 'Almeida, et al, 2007) are not presented. The male reproductive system in Callinectes amnicola is quite like that found in Callinectes sapidus (Cronin, 1947;Johnson and Otto, 1981), in the blue swimming crab, Portinus pelagicus (Stewart et al, 2010), in Paguristes eremita (Tirelli et al, 2010), in hermit crab Clibanarius sclopetarius, (Santos and Mantelatto, 2011), in Pea Crabs (Becker et al, 2013), in Callinectes ornatus (Do Nascimento and Zara, 2013). Soundarapandian et al (2013aSoundarapandian et al ( , 2013b indicate similar organs in the two species, Charybdis feriata and Portunus pelagicus.…”
Section: Cytology Of the Vasa Deferentiamentioning
confidence: 76%
“…The vasa deferentia of others adult crabs are divided into ducts or tubules. In Pinnotheres pisum and Nepinnotheres pinnotheres, the anterior vas deferens is composed of coiled tubules (Becker et al, 2013). In Charybdis feriata and Portunus pelagicus the vasa deferentia are pair coiled tubules (Soundarapandian et al., 2013a(Soundarapandian et al., , 2013b.…”
Section: Cytology Of the Vasa Deferentiamentioning
confidence: 99%
See 1 more Smart Citation
“…Later, both sexes moult into a well-calcified 'hard' stage that exhibits free-living adaptations facilitating to leave the host and move in the external environment (Hartnoll, 1972). Males reach sexual maturity in this stage (Becker, Klaus, & Tudge, 2013) but the ovary appears to be not yet developed in hard stage females (Becker, Brandis, & Storch, 2011). Hard-stage females recolonize the host and once inside they moult into the 'post-hard' stages (Atkins, 1926).…”
mentioning
confidence: 99%